OPTIMASI KOMPOSISI ORGANOCLAY UNTUK SIFAT MEKANIK KARET SINTETIS EPDM (ETHYLENE PROPYLENE DIENE MONOMER) - Yuliasari, Yuliasari; Fathurrohman, M. Irfan; Tjahjono, Arif; Andriani, Woro (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
EPDM - Clay Composite has been synthesized through the melt compounding process. EPDM type buna 6466 and sulfur are used respectively as polymer matrix and curing agent. Filler used is organoclay type cloisite 15 A, and EPDM - Clay composite characterized using XRD. Based on XRD results, undetectable peak d001 indicates that the basal space formed is large enough and signifies the formation of the exfoliation structure. The results of mechanical tests showed that the tensile strength and reinforcing index increased along with the addition of organoclay composition. Keywords: EPDM – Clay composites, organoclay, melt compounding, exfoliation